Reintroduction of Diazoxide after Diagnosis of Pulmonary Hypertension in a Patient with Transient Hyperinsulinism - Schweiger, Bahareh; Sanchez-Lara, Pedro A.; Markush, Dor; Nawathe, Pooja (Journal of Child Science, 2021)
Our case describes the reintroduction of diazoxide despite life-threatening pulmonary hypertension in our infant due to lack of therapeutic options for congenital hyperinsulinism.
Keywords: congenital hyperinsulinism; diazoxide; pulmonary hypertension; chlorothiazide; side effects